Hubungan Status Gizi dan Status Imunisasi dengan Kejadian Diare pada Balita di Puskesmas Putri Ayu Kota Jambi - Oktariana, Mela; Hariyanti, Reni; Riya, Rosa; Sulastri, Sulastri (Jurnal Ilmiah Ners Indonesia, 2023)
In Indonesia, the death rate for children under five due to diarrhea in 2015 was 8,600 children under five, which is ranked 12th out of 15 countries with the highest death rate for children under five in the world and the highest in Southeast Asia. The aim of the research was to determine the relationship between nutritional status and immunization status with the incidence of diarrhea at the Putri Ayu Health Center, Jambi City. This research method is quantitative with a retrospective approach. The population in this study were all toddlers at the Putri Ayu Community Health Center, Jambi City, totaling 483 people with a sample size of 73 respondents. The sampling technique uses random sampling. Data analysis uses univariate and bivariate analysis with statistical tests using the Chi-Square Test. The results of research that has been carried out show that there is a relationship between nutritional status and the incidence of diarrhea in toddlers with outcomes (p=0.046) and there is a relationship between immunization status and the incidence of diarrhea in toddlers with outcomes (p=0.004) at the Putri Ayu Community Health Center, Jambi City in 2023. It can be concluded that there is a relationship between nutritional status and immunization status with the incidence of diarrhea in toddlers at the Putri Ayu Community Health Center, Jambi City in 2023. Abstrak Di Indonesia angka kematian balita akibat diare pada tahun 2015 sebanyak 8.600 balita yang menempati peringkat 12 dari 15 negara dengan angka kematian balita tertinggi di dunia dan tertinggi di Asia Tenggara. Tujuan dilakukannya penelitian untuk mengetahui hubungan status gizi dan status imunisasi dengan kejadian diare di Puskesmas Putri Ayu Kota Jambi. Metode penelitian ini bersifat kuantitatif dengan pendekatan restrospektif. Populasi dalam penelitian ini seluruh balita di Puskesmas Putri Ayu Kota Jambi sebanyak 483 orang dengan jumlah sampel sebanyak 73 responden. Teknik pengambilan sampel menggunakan random sampling. Analisis data menggunakan analisis univariat dan bivariate dengan uji statistik menggunakan Uji Chi-Square. Hasil penelitian yang telah dilakukan didapatkan bahwa ada hubungan antara status gizi dengan kejadian diare pada balita dengan hasil (p=0.046) dan ada hubungan status imunisasi dengan kejadian diare pada balita dengan hasil (p=0,004) di Puskesmas Putri Ayu Kota Jambi Tahun 2023. Dapat disimpulkan bahwa ada hubungan status gizi dengan status imunisasi dengan kejadian diare pada balita di Puskesmas Putri Ayu Kota Jambi Tahun 2023.